Clonal dispersion of Acinetobacter baumannii in an intensive care unit designed to patients COVID-19 - Emilio Mariano Durán-Manuel; Clemente Cruz-Cruz; Gabriela Ibáñez-Cervantes; Juan Carlos Bravata-Alcantará; Oscar Sosa-Hernández; Laura Delgado-Balbuena; Gregorio León-García; Iliana Alejandra Cortés-Ortíz; Monica Alethia Cureño-Díaz; Graciela Castro-Escarpulli; Juan Manuel Vélez-Reséndiz; Juan Manuel Bello-López (Journal of Infection in Developing Countries)
Introduction: SARS-CoV2 pandemic marks the need to pay attention to bacterial pathogens that can complicate the hospital stay of patients in the intensive care unit (ICU). ESKAPE bacteria which includes Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter cloacae are considered the most important, because of their close relationship with the development of ventilator-associated pneumonia (VAP). The aim of this work was to identify and characterize ESKAPE bacteria and to detect their possible clonal spread in medical devices, patients, and medical personnel of the ICU for COVID-19 patients of the Hospital Juarez de Mexico.